Effects of Bone Young’s Modulus on Finite Element Analysis in the Lateral Ankle Biomechanics - W. X. Niu; L. J. Wang; T. N. Feng; C. H. Jiang; Y. B. Fan; M. Zhang (Applied Bionics and Biomechanics)
Finite element analysis (FEA) is a powerful tool in biomechanics. The mechanical properties of biological tissue used in FEA modeling are mainly from experimental data, which vary greatly and are sometimes uncertain. The purpose of this study was to research how Young’s modulus affects the computations of a foot-ankle FEA model. A computer simulation and an in-vitro experiment were carried out to investigate the effects of incremental Young’s modulus of bone on the stress and strain outcomes in the computational simulation. A precise 3-dimensional finite element model was constructed based on an in-vitro specimen of human foot and ankle. Young’s moduli were assigned as four levels of 7.3, 14.6, 21.9 and 29.2 GPa respectively. The proximal tibia and fibula were completely limited to six degrees of freedom, and the ankle was loaded to inversion 10° and 20° through the calcaneus. Six cadaveric foot-ankle specimens were loaded as same as the finite element model, and strain was measured at two positions of the distal fibula. The bone stress was less affected by assignment of Young’s modulus. With increasing of Young’s modulus, the bone strain decreased linearly. Young’s modulus of 29.2 GPa was advisable to get the satisfactory surface strain results. In the future study, more ideal model should be constructed to represent the nonlinearity, anisotropy and inhomogeneity, as the same time to provide reasonable outputs of the interested parameters.